KARAKTERISTIK PENDERITA PERCOBAAN BUNUH DIRI DENGAN RACUN DI RSUD DR. PIRNGADI KOTA MEDAN TAHUN 2006-2011 - Christivani MJ Pardede (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2012)
Suicide is a public health problem that is closely related to mental health. WHO 2006 report that every year in the world there are 10-20 million people commit suicide and 1 million of them died from suicide. This figure does not include suicide attempts up to 20 times more frequent than the incidence of suicide, and poison is one of the many methods used. To know the characteristics of patients attempted suicide by poison in hospitals Dr. Pirngadi Medan in 2006-2011, conducted research that is desktiptif a case series design. The study population numbered 116 people, and the same sample population. Data obtained from medical records, data analyzed by Chi-square test and Anova. The study found that in 2006-2011, the highest proportion of patients arriving at night 41.3%, 24.2% on Sunday, comes from the age group 15-29 years 69%, 69% female, 55.8% Protestant Christianity, a job as a student / lecture 29.6%, 50.5% unmarried, use toxic pesticides group 61.2%, the level of awareness when it arrives good 92.2 %, with diagnosis of psychosis disorder 62.9%, long maintainability average of 2 days, the own request of back home 68.1%, 82.8% use a personal cost. There were significant differences when at home statue (p = 0.001) based on the average treatment length. Suggested to the hospital in order to improve health care and psychological counseling to the patients attempted suicide. Expected to complete the medical record patient sociodemographic data recording and specifications of poisons are used. Keyword: Attempted suicide by poison, Characteristics, Dr. Pirngadi Hospital